1992
DOI: 10.1103/physreva.46.2539
|View full text |Cite
|
Sign up to set email alerts
|

Absolute triple differential cross section for ionization of helium near threshold

Abstract: Absolute measurements with an accuracy of 22% and theoretical results in a distorted-wave Born approximation (DWBA) are reported for the triple-differential cross section for 26.6-eV electron-impact ionization of helium. An apparatus is used that allows all scattering angles to be independently varied for both coplanar and noncoplanar geometries. The measurements are compared with a DWBA calculation that includes exchange distortion in the calculation of the distorted waves, as well as with earlier calculation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
71
1

Year Published

1993
1993
2006
2006

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 33 publications
15
71
1
Order By: Relevance
“…The new measurements are compared here with results of two theoretical approaches: the distorted partial wave (DPW) approach of Pan and Starace [4] and the convergent close coupling (CCC) approach of Bray et al [17]. At low energies, the DPW approach [4] has provided an interpretation of the observed differences in the (e, 2e) TDCS's for H and He [2] in terms of partial wave phase shifts; its predictions have also been found to be in excellent agreement with the first absolute TDCS results for He [7,8]. At high energies, the CCC approach [17,18] provides accurate results in excellent agreement with all experimental features.…”
supporting
confidence: 56%
See 2 more Smart Citations
“…The new measurements are compared here with results of two theoretical approaches: the distorted partial wave (DPW) approach of Pan and Starace [4] and the convergent close coupling (CCC) approach of Bray et al [17]. At low energies, the DPW approach [4] has provided an interpretation of the observed differences in the (e, 2e) TDCS's for H and He [2] in terms of partial wave phase shifts; its predictions have also been found to be in excellent agreement with the first absolute TDCS results for He [7,8]. At high energies, the CCC approach [17,18] provides accurate results in excellent agreement with all experimental features.…”
supporting
confidence: 56%
“…These showed that the shapes of the angular distributions depend on the target even though the asymptotic Coulomb fields experienced by the three final state particles are target independent. While theoretical calculations [3][4][5][6] were able to replicate reasonably well the experimentally observed (e, 2e) angular distributions, the first absolute measurements, for He [7,8], agreed with only two of these [4,6]. The implicit implication was that accurate accounting of target effects on the various electronic partial waves as well as treatment of electronelectron interactions are necessary to obtain agreement with absolute data and that omission of these effects can lead to disagreement with experiment by factors of 2-200 [9].…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…above 4 times the threshold) is based upon a large body of measurements, on various targets and in various kinematics (3293316) and is essentially complete. From this point of view it is interesting the survey of the interaction mechanism given in the paper by Rosel et al (34). The energy range covered is large and the evolution of the TDCS in coplanar symmetric conditions is followed continuously from the impulsive limit to the near threshold region.…”
Section: Interaction Mechanismmentioning
confidence: 98%
“…Unlike elastic electron-neutral atom collisions, differential cross sections are not readily available for inelastic electron-neutral atom collisions, though the situation is improving [6], [7]. The lack of this information led us to introduce a parameter h which is the fraction of the maximum possible 2 momentum of the electron(s) which is conserved in inelastic collisions (including ionizing collisions).…”
Section: > C R a R T (~O )mentioning
confidence: 99%